2021
DOI: 10.1007/s10461-021-03375-w
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Provider Preexposure Prophylaxis (PrEP) Training: A Cross-Sectional Analysis of Recommendations from Providers Across the PrEP Implementation Cascade

Abstract: Expanding PrEP access necessitates training that supports healthcare providers’ progression along the PrEP implementation cascade, moving from PrEP awareness to prescription. We surveyed 359 USA providers about PrEP training content and format recommendations. We examined the association between cascade location and training recommendations. Most providers were aware of PrEP (100%), willing to prescribe PrEP (97.2%), had discussed PrEP with patients (92.2%), and had prescribed PrEP (79.9%). Latent class regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…Although, as expected, prescribing providers had higher self-efficacy scores compared to nonprescribing providers, both groups were least confident in PrEP initiation compared to the other steps of PrEP care. This finding aligns with previous literature describing low PrEP prescription rates despite a high-level of provider awareness and support for PrEP in the United States [ 8 , 33 , 34 ]. Furthermore, other studies have suggested that decreased knowledge about insurance navigation (a component of the PrEP initiation step) stymies providers’ ability to prescribe PrEP [ 33 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although, as expected, prescribing providers had higher self-efficacy scores compared to nonprescribing providers, both groups were least confident in PrEP initiation compared to the other steps of PrEP care. This finding aligns with previous literature describing low PrEP prescription rates despite a high-level of provider awareness and support for PrEP in the United States [ 8 , 33 , 34 ]. Furthermore, other studies have suggested that decreased knowledge about insurance navigation (a component of the PrEP initiation step) stymies providers’ ability to prescribe PrEP [ 33 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings inform how provider training can be optimized and tailored to improve provider knowledge, attitudes, and self-efficacy in PrEP care [ 8 , 33 ]. Customized provider training has been associated with effective implementation of other healthcare interventions, such as improving negative attitudes towards buprenorphine prescription for opioid use disorder [ 32 ] and facilitating effective implementation of evidence-based tobacco use treatment in health centers [ 37 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In our research, we experienced the value of combining advice and instant feedback of routinized experts with peer discussions. A recent study from the U.S. also found that PrEP-experienced providers recommended interactive formats for future training initiatives on PrEP ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using telemedicine linked with home or community-based HIV and STI testing may reduce the burden of clinic visits [31], particularly for patients living in nonurban settings. Clinician training is critical and has been shown to increase rates of PrEP prescribing [37].…”
Section: Promoting Preexposure Prophylaxis As Both Decreasing Risk An...mentioning
confidence: 99%